2021
DOI: 10.12807/ti.113202.2021.a04
|View full text |Cite
|
Sign up to set email alerts
|

Exploring predictors of translation performance

Abstract: The study reported on examined the question of whether translators’ cognitive faculties might be able to predict their performance on a translation task. Research on individual cognitive differences in translation has been a new issue in the realm of Translation Studies. However, the majority of previous studies have targeted single cognitive faculties for the purpose of investigation and we therefore know little about how sets of cognitive faculties can affect the process of translation from one language into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…Their study implicated the significant role of emotional intelligence to gain a deeper understanding of translation and interpreting processes. Having used Waddington (2001) translation assessment rubric, Ghobadi et al (2021) investigated the predictability power of individual cognitive-emotional differences, including working memory, emotional intelligence, and, tolerance of ambiguity, in translation performance. They found that the interaction of these cognitive-emotional components predicts translation performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Their study implicated the significant role of emotional intelligence to gain a deeper understanding of translation and interpreting processes. Having used Waddington (2001) translation assessment rubric, Ghobadi et al (2021) investigated the predictability power of individual cognitive-emotional differences, including working memory, emotional intelligence, and, tolerance of ambiguity, in translation performance. They found that the interaction of these cognitive-emotional components predicts translation performance.…”
Section: Review Of Literaturementioning
confidence: 99%
“…While exploring the relationship between personality type and performance in translating expressive, appellative and informative texts, Shaki and Khoshsaligheh (2017) concluded that the sensing-type students delivered less successful performance than the intuitive-type students in all three tasks. Their performance was evaluated against Waddington’s (2001) rubric, which was also adopted by Ghobadi et al (2021) to assess participants’ translation performance. Meanwhile, some studies considered translation performance as the sum of behaviors that participants controlled in the process of translation ( Muñoz Martín, 2014 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As translation problems are individual and arise from the interplay between task properties and characteristics of task performers ( Muñoz Martín and Olalla-Soler, 2022 ), translators may deliver varied performance even on the same task. Studies that investigated the interplay between task properties and translator characteristics worked on such individual differences as L2 proficiency ( Pokorn et al, 2019 ), working memory capacity ( Wang, 2022 ), and emotional intelligence ( Ghobadi et al, 2021 ), among others. However, to the best of our knowledge, no study has so far investigated how task complexity influences the translation performance of students with different levels of self-efficacy belief, an important affective variable influencing students’ motivation and learning ( Bandura, 1997 ) and a construct recently introduced into translation studies ( Yang et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has proved that self-efficacy before performing search activities can affect the motivation for accomplishing the tasks and thus affect the final task performance (Ross et al, 2016). Secondly, translation is considered as a complex and high-cognitive activity affected by different types of factors such as translation self-efficacy (Rojo and Caro, 2018;Ghobadi et al, 2021). Therefore, translation selfefficacy during online information seeking can influence the allocation of cognitive resources and the amount of effort and perseverance to be applied to perform tasks, especially in the face of difficulties (Bolaños-Medina, 2014;Bolaños-Medina and Núñez, 2018).…”
Section: Introductionmentioning
confidence: 99%